Determinants of Regional Economic Growth: The Role of Infrastructure and Labor in Indonesian Provinces - Raihan Muzaki; Hastarini Dwi Atmanti (Journal of Economics and Business, 2026)
Infrastructure is one of the essential elements required to achieve desired economic growth. Infrastructure is a vital aspect in accelerating national development. Infrastructure is a crucial factor influencing Gross Regional Domestic Product (GRDP).The type of data used in this research is secondary data, combining time series and cross-sectional data, specifically from 34 provinces in Indonesia from 2017-2023. This study utilizes independent variables including road infrastructure (JLN), electricity infrastructure (LSK), water infrastructure (AIR), and labor (TK). The analytical method employed in this research is panel data regression.The results of this study indicate that electricity infrastructure, water infrastructure, and labor have a positive and significant effect on economic growth. However, observations show that road infrastructure does not affect economic growth.